2020
DOI: 10.1177/2319714520920798
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Co-operative Form’s Potential in Crowdfunding: A Non-monetary Perspective

Abstract: Technology-driven change has generated new, even revolutionary business models, characterized by high levels of user participation. In the finance field, business models based on crowdfunding have seen significant growth and entered use as an alternative means of extending access and gaining financing for various types of projects. Nonetheless, current crowdfunding practices have been subject to criticism for issues such as information asymmetry, lack of trust and transaction costs, spurring discussion of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Interestingly, an initiative has been recently taken by three labour activists and progressives to launch a driver-owned ride-sharing app-based platform, The Drivers Cooperative, as an alternative to platform companies (Nolan 2020). Its crowdfunding campaign for developing this initiative quickly reached its goal which hints at how information asymmetry and a lack of trust between funders and investors can be transcended by platform cooperativism and how this stimulates interaction between the future driver-owners and potential users (Talonen et al 2020).…”
Section: Case Studies On Location-based Platform Work: Chapters 15 To 20mentioning
confidence: 99%
“…Interestingly, an initiative has been recently taken by three labour activists and progressives to launch a driver-owned ride-sharing app-based platform, The Drivers Cooperative, as an alternative to platform companies (Nolan 2020). Its crowdfunding campaign for developing this initiative quickly reached its goal which hints at how information asymmetry and a lack of trust between funders and investors can be transcended by platform cooperativism and how this stimulates interaction between the future driver-owners and potential users (Talonen et al 2020).…”
Section: Case Studies On Location-based Platform Work: Chapters 15 To 20mentioning
confidence: 99%
“…For example, new peer‐to‐peer insurers have applied the special characteristics of mutual insurance companies in their business models (Lucas, 2017; Reardon, 2017; cf. Talonen et al, 2020a). In addition, it has been suggested that their community focus offer special potential for tackling the sustainable development challenges (Cambridge Institute for Sustainability Leadership [CISL], 2019).…”
Section: Introductionmentioning
confidence: 99%